Bioavailability of 2, 4, 6-Trinitrotoluene (TNT) to Earthworms in Three Different Types of Soils in China. Issue 1 (2nd January 2016) - Huang, Qing; Liu, Borui; Hosiana, Mwubahamana; Guo, Xiang; Wang, Tingting; Gui, Mingying
ABSTRACT: To study the effects of aging time (the length of time when contaminants are sequestered in soil) and soil properties on TNT bioavailability in soil, earthworms ( Eisenia fetida ) were exposed to three types of soils (fluvo-aquic soil, loessal soil, and black soil) contaminated by TNT for 7, 14, 21, 28, 35, and 42 days. The Earthworm-Soil Accumulation Factor (ESAF) of TNT and soil properties were analyzed. The ESAFs in black soil were significantly lower than those in fluvo-aquic soil and loessal soil (P < 0.05). In loessal soils, the ESAF increased with aging time, while that in black soils decreased. The ESAF of TNT had a significantly negative correlation with soil organic matter content, clay contents, and cation exchange capacity, which were the main factors affecting the TNT bioavailability in soils (P < 0.01). There was more quartz and feldspar in black soil, as well as more particles and micropores on the surface, which resulted in the easy adsorption and lower bioavailability of TNT. In conclusion, TNT bioavailability in soils is affected by aging time, soil physical and chemical properties, and mineral and surface properties, which must be considered when biotreatment for TNT in soils is applied.